Hazy borders: Legality and illegality across the US-Mexico border - Alberto Hernández Hernández (Journal of Illicit Economies and Development (JIED), 2021)
This paper analyzes the different trading networks, the flux of merchandise, and the actors involved in the act of crossing goods through the United States-Mexico border, particularly in the Tijuana-San Diego region. It argues that the line dividing both countries works differently depending on who travels through it, what kind of items are brought across, and which direction a person is going. These different patterns can be further analyzed when comparing northbound and southbound traffic; roughly speaking, products crossed into the US are usually prescription drugs, herbs, food, and cigarettes, among others; whereas, items crossed into Mexico are usually construction materials, electronics and electrodomestics, toys, marijuana, guns, and so forth. This paper proposes that the border is not a well-defined barrier when it comes to different types of merchandise, instead becoming hazy and allowing for the small-scale smuggling of products without incurring legal and/or problematic situations.
Keywords: 330; firearms; legality-illegality; narcotics; smuggling; US-Mexico border